Gewalt und Heldentum - Gölz, Olmo (Helden - Heroisierungen - Heroismen, 2020)
Heldenerzählungen berichten von Gewalt, dem vorsätzlichen Übergriff auf den Körper eines anderen gegen dessen Willen. In der Gewalttat kulminieren Mut und Entschlossenheit, Regelverachtung und Handlungsmacht, sie erscheint als Bewährungsprobe des Individuums. Gewalt zwingt die Beteiligten, sich zur ihr zu verhalten und zu positionieren - Täter wie Opfer, Beteiligte wie Beistehende, Zeitgenossen wie Nachkommende. In diesem Band strukturieren drei Perspektivierungen -zur Heroisierung, zum Ertragen und zur Vermeidung von Gewalt - literatur-, geschichts-, kulturwissenschaftliche und soziologische Zugänge zum Beziehungsgeflecht von Heldentum und physischer Gewaltausübung. Ein einleitender Aufsatz identifiziert theoretische Schnittstellen. Mit Beiträgen von Ronald G. Asch, Cornelia Brink, Ulrich Bröckling, Olmo Gölz, Joachim Grage, Felix K. Maier, Vera Marstaller, Christoph Mauntel, Sotirios Mouzakis, Friederike Pannewick, Jan Philipp Reemtsma, Sven Reichardt und Cornel Zwierlein. Heroic tales recount violence, which can be defined as a deliberate assault on the body of another against their will. The act of violence is a culmination of courage, determination, contempt for rules and the power to act; violence appears as a paradigmatic test of the individual. Violence forces those involved to position themselves in relation to it - perpetrators as well as victims, participants as well as bystanders, contemporaries as well as descendants. In this volume, three perspectives on the heroization, endurance and avoidance of violence structure different literary, historical, cultural and sociological approaches to identifying the relationship between the heroic and physical violence. An introductory essay identifies theoretical intersections between violence and heroism. With contributions by Ronald G. Asch, Cornelia Brink, Ulrich Bröckling, Olmo Gölz, Joachim Grage, Felix K. Maier, Vera Marstaller, Christoph Mauntel, Sotirios Mouzakis, Friederike Pannewick, Jan Philipp Reemtsma, Sven Reichardt and Cornel Zwierlein.